Preclinical Evaluation of Vemurafenib as Therapy for BRAF(V600E) Mutated Sarcomas - Gouravan, Sarina (Int J Mol Sci, 2018)
The BRAF(V600E) mutation, which in melanoma is targetable with vemurafenib, is also found in sarcomas and we here evaluate the therapeutic potential in sarcoma cell lines. Methods: Four sarcoma cell lines harboring the BRAF(V600E) mutation, representing liposarcomas (SA-4 and SW872), Ewing sarcoma (A673) and atypical synovial sarcoma (SW982), were treated with vemurafenib and the effects on cell growth, apoptosis, cell cycle progression and cell signaling were determined. Results: Vemurafenib induced a strong cytostatic effect in SA-4 cells, mainly due to cell cycle arrest, whereas only moderate levels of apoptosis were observed. However, a high dose was required compared to BRAF(V600E) mutated melanoma cells, and removal of vemurafenib demonstrated that the continuous presence of drug was required for sustained growth inhibition. A limited growth inhibition was observed in the other three cell lines. Protein analyses demonstrated reduced phosphorylation of ERK during treatment with vemurafenib in all the four sarcoma cell lines confirming that the MAPK pathway is active in these cell lines, and that the pathway can be inhibited by vemurafenib, but also that these cells can proliferate despite this. Conclusions: These findings indicate that vemurafenib alone would not be an efficient therapy against BRAF(V600E) mutated sarcomas. However, further investigations of combination with other drugs are warranted.